The Effect of Work Life Balance and Employee Engagement on Performance Through Knowledge Sharing of Employees of The Regional Development Planning, Research and Development Agency of Central Maluku Regency - Sariyati Sariyati; Conchita V. Latupapua; Gerrit M Pentury (Sean Institute, 2026)
This study aims to analyze the influence of Work Life Balance and Employee Engagement on employee performance through Knowledge Sharing among employees of the Regional Development Planning, Research and Development Agency (Bapplitbangda) of Central Maluku Regency. This study uses a quantitative approach with a survey method. The study population is all employees of Bapplitbangda of Central Maluku Regency, with a sampling technique using saturated sampling so that the entire population becomes research respondents. Data collection was carried out through distributing questionnaires measured using a Likert scale. Data analysis uses the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS) to test direct and indirect relationships between variables. The results of the study indicate that Work Life Balance has a positive and significant effect on Employee Engagement and Knowledge Sharing. Employee Engagement has a positive and significant effect on Knowledge Sharing and employee performance. Knowledge Sharing was not proven to have a positive and significant effect on employee performance. In addition, Knowledge Sharing is able to mediate the influence of Work Life Balance and Employee Engagement on employee performance. The implications of this study emphasize the importance of strengthening policies that support work-life balance, increasing employee engagement, and developing a culture of knowledge sharing to improve the performance of Bapplitbangda Central Maluku Regency employees in a sustainable manner.